Data from: Increased annual methane uptake driven by warmer winters in an alpine meadow - Wang, Peiyan (Dryad, 2022)
Pronounced non-growing season warming and changes in soil freeze-thaw
(F-T) cycles can dramatically alter net methane (CH4) exchange rates
between soils and the atmosphere. However, the magnitudes and drivers of
warming impacts on CH4 uptake in different stages of the F-T cycle are
poorly understood in cold alpine ecosystems, which have been found to be a
net sink of atmospheric CH4. Here, we reported a year-round ecosystem
daily CH4 uptake in an alpine meadow on the Qinghai-Tibetan Plateau after
a five-year warming experiment that included a control, a low-level
warming treatment (+2.4℃ at 5 cm soil depth), and a high-level warming
treatment (+4.5℃ at 5 cm soil depth). We found that warming shortened the
F-T cycle under the low-level warming and soils did not freeze under the
high-level warming. Although both warming treatments increased the mean
CH4 uptake rate, only the high-level warming significantly increased
annual CH4 uptake compared to the control. The warming-induced stimulation
of CH4 uptake mainly occurred in the cold season, which was mostly during
spring thaw under low-level warming and during the frozen winter under
high-level warming due to a longer period with thawed soil. We also found
that warming significantly stimulated daily CH4 uptake mainly by reducing
near-surface soil water content in the warm season, whereas both soil
water content and temperature controlled daily CH4 uptake in different
ways during the autumn freeze, frozen winter, and spring thaw periods of
the control. Our study revealed a strong warming effect on CH4 uptake
during the entire F-T cycle in the alpine meadow, especially the unfrozen
winter. Our results also suggested the important roles of soil pH,
available phosphorus, and methanotroph abundance in regulating annual CH4
uptake in response to warming, which should be incorporated into
biogeochemical models for accurately forecasting CH4 fluxes under future
climate scenarios.
Ecosystem methane flux, and soil moisture and soil temperature at 5 cm, 15
cm, 30 cm soil depths were observed for an entire F-T cycle from June 2019
to June 2020 in a typical alpine meadow on the Qinghai- Tibetan
Plateau (QTP), where a long-term warming experiment was established in
2014. Soil temperature and VWC at all three depths from June 2019
to June 2020 were analysed and used in this study, and soil temperature at
5 cm depth from June 2016 to June 2021 was included in
the supplemental materials to support the results.
Precipitation was recorded at 30-min intervals by the Hongyuan county
weather station. The warming experiment included three
treatments: ambient temperature (CK), low-level warming
(LW, +2.4℃ at 5 cm soil depth), and high-level warming
(HW, +4.5℃ at 5 cm soil depth). The
measurement intervals between treatments were 5−20
mins and all data were daily averaged for data analysis
in the paper. Methane uptake was gap-filled by using a random
forest algorithm in R.  Soil F-T cycle for each
plot of all treatments were divided into the following stages: thawed,
freezing, frozen, and thawing (Figure 1d) according to the definitions
used in previous studies (Zona et al., 2016; Taylor et al., 2018; Arndt et
al., 2019, Bao et al., 2021). Specifically, the thawed stage was
when daily mean soil temperature at 5 cm depth (daily mean T_soil
at 5 cm) was > 0.75℃ for at least five consecutive days.
The frozen stage was when daily mean T_soil at 5 cm was < −0.75℃
for at least five consecutive days. The freezing and thawing stages were
defined as freezing-frozen and frozen-thawing transition periods,
respectively, when daily mean T_soil at 5 cm was between −0.75℃
and 0.75℃ (Figures 1b, d and Table S1). According to these F-T stages, all
of which occurred in the control plots, we divided our measurements into
four seasons: autumn freeze (Saf), frozen winter (Sfw), spring thaw (Sst),
and warm season (WS). The cold season (CS) included autumn freeze, frozen
winter, and spring thaw. Mineral soil samples were obtained from depths of
0−10 cm, 10−20 cm, and 20−40 cm from each plot in August 2020 for soil
chemical and microbial analyses including soil pH, available phosphorus
(AP), soil total carbon (TC) and nitrogen (TN) contents, soil microbial
biomass carbon (MBC) and nitrogen (MBN) and methanotrophs abundance.
Keywords: FOS: Biological sciences; experimental warming; freeze-thaw cycle; CH4 uptake; soil water content; soil temperature; Soil pH; soil available phosphorus; methanotroph